The role of Sepedi poetry in teaching and learning grade 10 grammar aspects at Kgakotlou Circuit, Capricorn South District, Limpopo Province, South Africa - Rabore, Mahlatse Daniel (My University, 2024)
The study aimed to explore the role of Sepedi poetry in teaching and learning Grade 10 grammar aspects. Poetry is deemed an efficacious resource tool for language teaching in the classroom as it teaches language skills: reading, writing, speaking, and listening. Reader response theory served as the lens to underpin the study, and the phenomena are viewed through the interpretivism paradigm. The study adopted a qualitative approach and a case study design. Data were collected through document analysis, observation, and semi-structured interviews, with purposively sampled teacher and learner participants. Data were analysed through the didactic method of the thematic data analysis approach. The findings revealed that teaching grammar aspects through poetry is advantageous as learners interact and relate well with poetry as part of their daily cultural practices, therefore having it in their formal education makes teaching and learning of language grammar effective. The study will benefit learners, teachers, and curriculum developers on the importance of poetry texts in teaching grammar aspects.
Thesis (M. Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Poetry; Grammar aspects; Role of poetry in teaching; Sepedi poetry; Language poetry; Poetry -- Study and teaching (Secondary); Sepedi language -- Study and teaching; Sepedi language -- Grammar -- Study and teaching (Secondary)